Anatomía foliar y del peciolo de especies de Pterigota (Sterculioideae; Malvaceae) - Chukwuma, Emmanuel Chukwudi; Soyewo, Luke Temitope; Okanlawon, Tolulope Fisayo; Ugbogu, Omokafe Alaba (Anales de Biología, 2017)
Leaf and petiole anatomy of Pterygota species in Nigeria were studied and their distribution within the area is also reported, following outlined standard protocols. They are chiefly distributed in Southern Nigeria especially in wetter areas. Foliar micro-characters showed that the species are hypostomatic and generally paracytic, more abundant in P. berquaertii, with an average of 115/mm² , than in P. macrocarpa, where it is 59/mm² . Epidermal cells are irregular, rectangular and polygonal. Petiole spherical with uniseriate epidermis; cell distribution ranging from solitary to radial multiples. This study has provided valuable information about these indigenous species. Further systematic studies are vital to understand the number and timing of independent evolution of the species into Nigeria.